Historical Notes on the Constitution and Judges in Colombia in the 19th Century - Andrés Botero-Bernal (Journal on European History of Law)
To understand how the judges, in general, lived the Constitution during the 19th Century, other phenomena that have been gradually forgotten by the dogmatic constitutionalists should be included, apart from the judgment of Judge Marshall of 1803 and the constitutional courts of Kelsen during the interwar period. Among them, it will be stated (a) that the ruling of 1803 was not a judgment that came out of nowhere, but one that followed a judicial career already marked by previous judgments, (b) that Kelsen did not act alone in proposing constitutional courts and (c) that the constitution was understood also as a relevant legal standard in Hispanic America throughout the 19th Century. This paper will focus on the third point but in the Colombian case. This requires considering how the constitution was lived at the time, to understand the value that the norm had in the liberal century. The forgetfulness or silencing referred to in this work is due to cultural colonialism, which affected, and continues to affect the Hispanic American legal culture./p>